Stem cell research - Skancke, Jennifer (Farmington Hills, MI : Greenhaven Press, 2009)
From the Publisher: Over thirty-five years ago, Greenhaven Press began publishing the Opposing Viewpoints series to help students gain an awareness of current issues and develop critical thinking skills. The Introducing Issues with Opposing Viewpoints series continues that tradition, presenting a wealth of information on contemporary issues in a colorful, easy-to-read format. In addition to pro/con articles, each Introducing Issues with Opposing Viewpoints volume includes appealing features designed to help students understand the complexities of current issues.
Foreword -- Introduction -- Chapter 1: Is Stem Cell Research Moral? -- 1: Stem cell research is immoral / William L Saunders Jr -- 2: Stem cell research is moral / Robert Menendez -- 3: Embryos used in stem cell research are human beings / William L Saunders Jr -- 4: Embryos used in stem cell research are not human beings / Michael J Sandel and Paul McHugh -- 5: Stem cell research is murder / Judie Brown -- 6: Stem cell research is not murder / David Holcberg and Alex Epstein -- Chapter 2: Can Stem Cell Research Cure Disease? -- 1: Stem cell research can cure many diseases / Barack Obama -- 2: Benefits of stem cell research have been exaggerated / Richard M Doerflinger -- 3: Alternatives to embryonic stem cell research can cure disease / David Christensen -- 4: Alternatives to embryonic stem cell research cannot effectively cure disease / Coalition for the Advancement of Medical Research -- 5: Stem cells made from skin are effective / Bernadine Healy -- 6: Stem cells made from skin are not effective / Sharon Begley -- Chapter 3: What Role Should Government Play In Stem Cell Research? -- 1: Government should fund stem cell research / Julie Hutto -- 2: Government should not fund stem cell research / Steve Lonegan -- 3: State governments will fund stem cell research if the federal government does not / Ronald Bailey -- 4: Stem cell research policies hurt the United States / Barbara A Mikulski -- 5: Stem cell research policies do not hurt the United States / Eric Cohen -- Facts about stem cell research -- Glossary -- Organizations to contact -- For further reading -- Index -- Picture credits.
Includes bibliographical references (p. 147-151) and index.
Keywords: Stem cells; Stem cells -- Research; Stem cells -- Social aspects